Hubungan Motivasi Kompensasi Dengan Kinerja Perawat Di RSUD Leuwiliang Tahun 2021: The Relationship of Compensation Motivation with Nurse Performance - Rahayu, Siti (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: The performance of nurses is an outcome that has been done in order to achieve organizational goals including the performance of each individual and working group that is implemented legally, not unlawfully, and in accordance with the morals and responsibilities imposed on him. This study aims to find out the relationship of compensation motivation to the performance of Leuwiliang Hospital nurses in 2021. Methods: The research used is correlation analysis with cross-sectional approaches and data analysis using chi-square. The population in the study was 248 nurses. The samples were taken with a simple random sampling technique on 150 non-ASN nurses. The instrument used is a questionnaire.  Results: Of the 112 nurses who lacked motivation, there were 111 (74.0%) who had poor performance. Of the 38 nurses with good motivation, 8 (5.3%) had a good performance. Of the 141 nurses whose compensation was less, 136 (90.7%) had poor performance. Of the 9 nurses with good compensation, 4 (2.7%) had a good performance. The results of the analysis of the relationship between motivation and nurse performance obtained an OR value of 29.600 with a p-value = 0.000 (a = 0.05), then there is a relationship between motivation to nurse performance. From the results of the analysis of the relationship between compensation and nurse performance, the OR value is 21.760 with p-value = 0.001, so there is a relationship between compensation and nurse performance. Discussion: Perceptions of Compensation Motivation have a close relationship with Nurse Performance